Kelimpahan Wereng Hijau, Insiden Penyakit Tungro, dan Efektivitas Sumber Inokulum pada Ketinggian Tempat Berbeda - Dini Yuliani (Institut Pertanian Bogor, 2014)
Rice Tungro disease is one of biotic constraint that can reduce yield potential of rice. Tungro disease viruses are transmitted from one plant to another by leafhoppers that feed on tungro-infected plants. The most efficient vector is the green leafhopper, Nephotettix virescens. Green leafhoppers (GLH) generally found in areas with high altitude and low temperature. However, GLH and tungro disease can be found in medium and low altitude areas. The aim of this study was to determine the abundance of green leafhopper, tungro disease incidence, and effectiveness of inoculum source in different altitude at endemic areas. Field observations conducted to observe tungro disease incidence and the density of GLH population. Moreover, greenhouse activities were conducted to examine the effectiveness of inoculum sources, including ratoon, spilled grain, weeds, and plants in the vegetative phase. The results showed there was no significant difference in the GLH population dynamics in upland areas represented by Garut and lowland areas represented by Purwakarta, both showed low population density. Ratoon, spilled grain, and plants in the vegetative phase were the effective inoculum sources to be used as host tungro viruses.